2019
DOI: 10.1007/s11356-019-04811-0
|View full text |Cite
|
Sign up to set email alerts
|

Body size variation of the ant Lasius niger along a metal pollution gradient

Abstract: The phenotypic diversity of ant workers plays a fundamental role in their biology. In this study, we asked if the body size variation of monomorphic workers of the ant Lasius niger (Formicidae) responds adaptively to metal pollution in a post-mining metal-polluted area. Nest samples of workers were collected along a pollution gradient to calculate the within-colony variance in body size (expressed as maximum head width, HW). The results showed that the body size variation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Petal 1978;Nahmani and Lavelle 2002;Migliorini et al 2004). Although metal pollution may reduce ant colony size and survival, ants are known to be relatively resistant to metal pollution in comparison with other groups of epigeic fauna due to their ability to regulate their internal metal contents (Grześ 2009;Grześ et al 2019). Ants are "soil engineers", that is, edaphic organisms that are able to modulate the resources to other organisms through their mechanical activities (Folgarait 1998;Cammeraat and Risch 2008;Farji-Brener and Werenkraut 2017;Viles et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Petal 1978;Nahmani and Lavelle 2002;Migliorini et al 2004). Although metal pollution may reduce ant colony size and survival, ants are known to be relatively resistant to metal pollution in comparison with other groups of epigeic fauna due to their ability to regulate their internal metal contents (Grześ 2009;Grześ et al 2019). Ants are "soil engineers", that is, edaphic organisms that are able to modulate the resources to other organisms through their mechanical activities (Folgarait 1998;Cammeraat and Risch 2008;Farji-Brener and Werenkraut 2017;Viles et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the experimental colonies produced with workers from three source colonies were more diverse than the control colonies in terms of genetic background and size variation. This is expected, as genetic effects on worker size and morphology have been reported in multiple species of ants [84][85][86] and worker size differs among colonies in L. niger 87 . Worker size and genetic background both influence the response threshold of individual workers 28,84,[88][89][90] , and worker size polymorphism is generally associated with improved division of labor [91][92][93] .…”
Section: Discussionmentioning
confidence: 55%
“…We confirmed that our experimental manipulation increased size variation in the more diverse colonies. Such size diversity could stem from genetic differences across colonies, but could also be explained by environmental and maternal effects 84,85,87,101 . The genetic background affects size and morphology in eusocial insects [84][85][86] , thus one strategy to increase worker size diversity is to increase genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the experimental colonies produced with workers from three source colonies were more diverse than the control colonies in terms of genetic background and size variation. Genetic effects on worker size and morphology have been reported in multiple species of ants [ 67 69 ] and worker size differs among colonies in L. niger [ 70 ]. Worker size and genetic background influence the response threshold of individual workers [ 30 , 67 , 71 73 ], and worker size polymorphism is generally associated with improved division of labor [ 74 76 ] (but there were contradictory results [ 77 , 78 ]).…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that our experimental manipulation increased size variation in the more diverse colonies. Such size diversity could stem from genetic differences across colonies, but could also be explained by environmental and maternal effects [ 67 , 68 , 70 , 97 ]. The genetic background affects size and morphology in eusocial insects [ 67 69 ], thus one strategy to increase worker size diversity is to increase genetic diversity.…”
Section: Discussionmentioning
confidence: 99%